Iowa Birdline update, February 11, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for February 11, 1991. Highlights include a Gyrfalcon and a Great Black-backed Gull. Epson - sheet feed/flatbed